การหาการกัดกร่อนของพื้นผิวคอนกรีตกำบังรังสีจากอันตรกิริยากับโลหะผสม เหล็ก ตะกั่ว ดีบุก บิสมัทหลอมเหลว - ศึกษิต แสงแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The research work studied acute surface corrosion of concrete due to the interaction with molten Fe-Pb-Sn-Bi alloy in order to provide preliminary data for nuclear safety analysis. The main parameters under study were concrete types and ratio between iron and molten Pb-Sn-Bi alloy (Fe:LM). Two types of radiation shielding concrete, ordinary concrete and heavy concrete composing of barite, were fabricated with 417.5 kg/cm² and 386.5 kg/cm2 average compressive strengths, respectively. Gamma ray attenuation coefficients at 0.662, 1.170 and 1.330 MeV were 0.1916, 0.1518 and 0.1340 cm⁻¹ for the ordinary concrete, and 0.2382, 0.1787 and 0.1654 cm⁻¹ for the heavy concrete. A plasma arc furnace (PAF) with 13 kW of power was constructed for laboratory-scale metal melting. Results of concrete corrosion from gamma radiography and physical sectioning revealed that the fabricated ordinary concrete and heavy concrete exhibited minor surface corrosion when interacting with 50 cm³ of molten Fe-Pb-Sn-Bi alloy. The corrosion was uniform throughout the surface of the concrete undergoing interaction with the molten alloy. The maximum corrosion took place with 100 wt.% Fe composition, while the minimum corrosion took place with 100 wt.% LM composition. The small volume of the molten metal alloy interacting with the concrete and the higher latent heat of fusion for iron than LM resulted in more observable corrosion. Therefore, molten iron was an important factor on concrete corrosion, while LM did not exhibit significant